Pengaruh Sistem Rekrutmen dan Pemberian Kompensasi terhadap Kinerja Karyawan Sukarela (TKS) Rumah Sakit Abdul Moloek Provinsi Lampung - Tri Nutri Andayati; Evi Meidasari (Ekonomi dan Bisnis, 2018)
The phenomenon that occurs in recruiting and providing compensation for the performance of employees in hospitals in recruiting employees and providing compensation for performance, employees of the Abdul Moloek Hospital are still not running openly so there are still many employees who have not felt satisfied, and compensation for non-medical employees is still often late (not on time) From the description of the background of the above problems the author will do Based on the formulation, the research objectives to be achieved are as follows: To find out the effect of Recruitment on employee performance of Voluntary Workers in Abdul Molok Hospital? To find out the effect of compensation on the performance of employees of Voluntary Workers in RS.Abdul Moloek Lampung Province? To determine the effect of recruitment and compensation on the performance of employees of the Voluntary Workers Hospital. Abdul Moloek Lampung Province From the results of this study it can be drawn a conclusion that: Recruitment variables have a persistent effect on employee performance by proving T count> T table (2,319> 1,666) with significant 0,002 <0,05) Compensation variables have a persistent effect on employee performance with proof of T count> T table (8,754> 1,666) with significant 0,000 <0,055) Recruitment and Compensation variables influence Simultaneously on employee performance by proving F count> F table (80,441> 3.12) with significant 0,000 <0,05) Recruitment, and compensation affects the performance of Abdul Moloek Hospital employees by 69.07%, and the remaining 30.3% is influenced by other variables